2011
DOI: 10.1007/s00701-011-1126-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously occurring tumours within the same cerebello-pontine angle: refining literature definitions and proposal for classification

Abstract: We report on an unusual case of a patient, not affected by neurofibromatosis, harbouring two radiologically spatially contiguous tumours within the same cerebello-pontine angle. Pathological findings were consistent with the diagnosis of two spatially distinct primary tumours, namely a meningioma and a schwannoma. We proposed a classification of tumours occurring at the same location consistent with the different spatial arrangement and histological nature of these conditions. The correct classification of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Vestibular schwannoma and meningiomas are the two most common lesions and account for 85 to 90% of all CP angle tumors. According to Frassinito et al, 6 two lesions, separately occurring but in close contact, should be considered an intermediate condition between concomitant and collision tumor and might be called a "contiguous tumor." Various theories have been proposed in the literature for the coexistence of two distinct primary brain tumors such as (1) coincidental development, (2) a single shared carcinogenic stimulus, (3) metaplasia in the original tumor or differentiation of the same cell line into various neoplastic elements, (4) collision of two separate tumors, and (5) a residual embryonic structure developing into two separate tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Vestibular schwannoma and meningiomas are the two most common lesions and account for 85 to 90% of all CP angle tumors. According to Frassinito et al, 6 two lesions, separately occurring but in close contact, should be considered an intermediate condition between concomitant and collision tumor and might be called a "contiguous tumor." Various theories have been proposed in the literature for the coexistence of two distinct primary brain tumors such as (1) coincidental development, (2) a single shared carcinogenic stimulus, (3) metaplasia in the original tumor or differentiation of the same cell line into various neoplastic elements, (4) collision of two separate tumors, and (5) a residual embryonic structure developing into two separate tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Frassanio et al reported spatial association of primary or metastatic tumours in cerebellopontine angle occurring simultaneously, which were referred to generically as 'simultaneous tumours' or 'collision tumours' making compartmentalization of these distinct nosologic entities difficult. 3 The possible pathogenesis behind the occurrence of distinctly demarcated or intermingled components of schwannoma and meningioma tissue is not clear. The concurrent occurrence of two tumours in the same location might result from the simultaneous growth of two separate tumours, metaplastic changes in the original tumour leading to formation new tumours from the metaplastic areasor bidirectional differentiation of the same progenitor cell line into two neoplastic elements.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous or contiguous tumors must be differentiated from mixed tumors which are schwannomas associated with meningeal cell proliferation reported to occur in about 21% of NF2 patients. [2,3,12] Our patient is a case of "contiguous tumor" as the tumor was radiologically indistinguishable but histologically distinct.…”
mentioning
confidence: 83%
“…The simultaneous occurrence of different tumors in the same location may occur due to metaplasia in the original tumor, collision of two different tumors, or differentiation into various cell lines from a common progenitor. [8,12] Till date, however, there is no evidence of a common progenitor cell for schwannoma and meningioma. Meningothelial reaction or hyperplasia adjacent to the main tumor (schwannoma) has been proposed as a plausible mechanism for such an occurrence and may have been responsible for contiguous tumors in our case.…”
mentioning
confidence: 99%